Zabedosertib, a novel interleukin-1 receptor-associated kinase-4 inhibitor, shows a favorable pharmacokinetic and safety profile across multiple phase 1 studies - Feldmüller, Maximilian; Jodl, Stefan J.; Ploeger, Bart; Wagenfeld, Andrea; Wiesinger, Herbert; Zollmann, Frank S.; Klein, Stefan; Zhang, Ruiping; Rohde, Beate; Höchel, Joachim (Frontiers in Pharmacology, 2025)
IntroductionZabedosertib, the interleukin-1 receptor-associated kinase-4 (IRAK4) inhibitor, is in clinical development as an oral therapeutic for immune-mediated inflammatory diseases and was thoroughly investigated in several phase 1 studies in healthy male volunteers.MethodsPharmacokinetics, safety, and tolerability of zabedosertib were characterized in two clinical phase 1 studies with single oral doses up to 480 mg and multiple oral doses up to 200 mg twice daily over 10 consecutive days. The absolute oral bioavailability was determined in a third study using the intravenous microtracer methodology.ResultsZabedosertib showed good safety and tolerability without dose-limiting toxicities or severe infections. An under-proportional increase in exposure was observed with increasing dose. The observed mean accumulation ratios for the area under the concentration–time curve of 1.04–1.62 were lower than expected based on the dose-independent terminal half-life of 19–30 h. The absolute oral bioavailability was 74% at a dose of 120 mg. No food effect was observed. The pharmacokinetics could be described with a one-compartmental population-pharmacokinetic model with first-order elimination, dose-dependent bioavailability, and capacity-limited binding in plasma. The estimation of target occupancy, based on in vitro potency for IL-6 inhibition as a representative pro-inflammatory cytokine in a human whole-blood assay, target residence time, and unbound plasma pharmacokinetics, indicated ∼80% target occupancy over the dosing interval after the maximum feasible dose of 120 mg twice daily. This dose was the highest dose providing relevant exposure increases.ConclusionBased on the projected target occupancy, favorable pharmacokinetics, and safety profile, as well as on distinct pharmacodynamic effects in a proof-of-mechanism study, zabedosertib 120 mg twice daily was selected for further clinical development in patient studies.Clinical trial registrationhttps://clinicaltrials.gov/, identifier SAD: NCT03054402, MAD: NCT03493269 (part 1), FE/abs.BA study NCT03244462 (EudraCT numbers: 2016-002668-15, 2017-001817-10, and 2016-004393-18).